An international focus on cardiac surgery nursing: student perspectives. (2nd August 2020) - Fredericks, Suzanne; Wynne, Rochelle; Martorella, Geraldine; Ramage, Naomi; Sawyer, Christine; Aniello, Autumn; Sanders, Julie
Abstract : This six-paper series in the International Year of the Nurse and Midwife aims to draw together two important themes: celebrating the role of nursing in advancing care in cardiac surgery and providing an international perspective of cardiac surgery nursing.